Endoscopic Characteristics of Small-Bowel Gastrointestinal Stromal Tumors Detected During Single-Balloon Enteroscopy: A Retrospective Analysis - Zuo, Xueyong; Guan, Zhong; Zhuang, Yun; Chen, Jianping; Wang, Mei (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The endoscopic features of small-bowel gastrointestinal stromal tumors (GISTs) are not well defined. The objective of this study was to describe the endoscopic features of GISTs of the small intestine detected via single-balloon enteroscopy (SBE). Materials and Methods: Patients with surgically confirmed small intestinal GISTs from January 2014 to September 2022 were retrospectively analyzed. The hospital’s electronic medical record system was used to retrieve the patients’ data, including their demographics, clinical symptoms, hemoglobin on admission, endoscopic and computerized tomography findings, clinicopathological findings, and surgical management data. Results: In total, 46 GIST patients (23 men and 23 women) with overt bleeding were included, with a mean age of 52 years (23-80 years). The typical duration of the symptoms was 48 hours. Four patients (8.70%) had lesions in the duodenum, 32 (69.56%) had lesions in the jejunum, 8 (17.39%) had lesions in the ileum, and 2 (4.35%) had lesions around the junction of the jejunum and ileum. Out of the 46 patients, 27 underwent SBE, and GISTs were visualized in 25, while the lesions could not be visualized in the remaining 2. Submucosal round (n = 13), submucosal sessile (n = 8), and invasive/penetrating (n = 4) were among the endoscopic tumor features. Twenty patients exhibited submucosal protuberant lesions, with ulceration, vascular nodules/congestion, or erosion on the surface, and 5 patients presented ulcerative infiltrative lesions. The multiple logistic regression analysis indicated that the invasive/penetrating characteristics of GISTs under SBE evaluation are significantly correlated with the risk level of GIST malignancy (P < .05). Conclusion: A variety of endoscopic characteristics could be observed during the preoperative SBE evaluation of small-intestine GISTs. Cite this article as: Zuo X, Guan Z, Zhuang Y, Chen J, Wang M. Endoscopic characteristics of small-bowel gastrointestinal stromal tumors detected during single-balloon enteroscopy: A retrospective analysis. Turk J Gastroenterol. 2024;35(5):354-359.